POWER AND NARRATION IN AMERICAN SUPERHERO IN SPIDERMAN SECRET OF THE SINISTER SIX BY ADAM TROY CASTRO’S - Hasan, Khoirul (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2014)
Spiderman Secret of The Sinister Six by Adam Troy Castro illustrated that superheroes as representation of sciences, power, and superiority. Superhero novel is very phenomenal for child to adult. Narration that are creating in this novel, trigger of understanding and believe that superhero as superior than Supervillain. So the aimed of deconstruction of superhero power to supervillain power. This research is use structuralism by Levi- Straus and deconstruction by Derrida, theory as a fundament of finding binary opposition for deconstruction analysis, and found the implied potensial meaning from this deconstruction. The result is first, Spiderman represented about American superiority, the narration created to strengthen and consolidate World's superpower had endured as American power. Narration about American power also created to discredit of Non-American. Although in this research is known that America is not entirely super power even tends to be weak, their power is affected by the allied countries. And their power is only found in countries that are experiencing economic instability and security. Second, Sinister Six represented as Non-American. They are always as a marginal group in international conference. But their inferiority (Non-American) in the world, they were trying to created technology or weapons defense system and war. They will create a tool to emulate the power owned by Americans. This work is to protect its citizens from regulations who are discredit their group. The deconstruction has been done earlier showed that the Sinister Six gang (Non-America) is a group of Superior, Good, and Loyal. While Spideman (America) is inferior class, Evil, and Rebellion.